Effects of Krill Oil and Race Distance on Serum Choline and Choline Metabolites in Triathletes: A Field Study - Storsve, Andreas B.; Johnsen, Line; Nyborg, Christoffer; Melau, Jørgen; Hisdal, Jonny; Burri, Lena (Frontiers in Nutrition, 2020)
Choline is an essential nutrient that has been implicated in athletic performance due to its role in maintaining normal muscle function. The concentration of free choline in serum has been shown to decrease during long-distance high-intensity exercise, yet few nutritional strategies to counteract this potentially performance-depleting loss in choline have been investigated outside the laboratory. This exploratory field study was performed to investigate if pre-race supplementation with phosphatidylcholine from krill oil can counteract the expected drop in choline and some of its metabolites during triathlon competitions. Forty-seven triathletes, 12 females and 35 males ranging in age from 25 to 61, were recruited from participants in the Ironman-distance Norseman Xtreme triathlon and the Sprint/Olympic-distance Oslo Triathlon. Twenty-four athletes were randomly allocated to the krill oil group, receiving 4 g of SuperbaBoostTM krill oil daily for 5 weeks prior to the race, and 23 athletes were randomly allocated to the placebo group, receiving 4 g of mixed vegetable oil daily. Blood samples were obtained before the race, immediately after completion of the race, and the day after the race for analysis of choline and its metabolites. The results showed that serum free choline concentrations significantly decreased from pre-race to race finish in all races, with a more pronounced decrease observed in the Ironman-distance Norseman Xtreme triathlon (34 %) relative to the Olympic/sprint-distance Oslo Triathlon (15 %). A decrease in betaine was also observed, while dimethylglycine (DMG) concentrations remained stable across all time points. Significantly higher concentrations of choline (9.4 % on average) and dimethylglycine (21.4 % on average) was observed in the krill oil compared to the vegetable oil group, and the krill oil group showed a significantly greater increase in serum free choline following race completion. In conclusion, krill oil may help to prevent that plasma choline concentrations become limiting during competitions.